Reliability of the endurance test for the erector spinae muscle - Cíntia Pereira de Souza; Renato Sobral Monteiro-Junior; Elirez Bezerra da Silva
Abstract Introduction: The low resistance of the erector spinae has been seen as a risk factor for developing chronic low back pain. The test of the erector spinae muscle endurance advocated by Biering-Sorensen has been used to assess the strength of the erector spinae muscle. Modifications of the measuring instrument require reliability studies. Objective: To evaluate the measurement of the erector spinae muscle endurance and the standard error of measurement (SEM) of the modified Biering-Sorensen test of erector spinae in women with chronic low back pain. Methods: Forty-eight sedentary women, aged 52 ±7, suffering from chronic low back pain, were tested. The position adopted was the prone position without the trunk on the examining table. Fixations were performed with straps at the ankles, knees and pelvis. The patient was instructed to maintain the shoulder blades in contact with the stadiometer as long as possible. The measurement was repeated, with measures 15 minutes apart. Results: Considering the confidence limits of Bland & Altman, - 40 and 68 seconds, the SEM was13 seconds and SEM% was 22. The ICC = 0.87 with p = 0.001. The first test was equal to 54 ± 36 seconds, and the retest = 67 ± 40 seconds. Conclusion: The endurance test of the erector spinae showed moderate reliability. Therefore, we suggest that, despite its applicability in clinical practice, the results should be interpreted carefully because the differences in mean erector spinae endurance of up to 13 seconds may be related to measurement error.